Social development in childhood and adolescence a contemporary reader - Killen, Melanie; Coplan, Robert J. 1967- (Chichester, West Sussex, UK Wiley-Blackwell, 2011)
"The field of social development examines some of the most fascinating topics of current research in psychology: the social nature of humans, the origins of morality, the nature of prejudice in childhood, bullying and victimization, the role of emotions in development and communication, and characteristics of healthy and unhealthy peer and parent-child relationships. This book brings together the most significant classic and contemporary writings in this area to provide a comprehensive overview of the field in a format that is both engaging for students and intuitive for instructors. Integrating the most important articles with tools to help students understand the material, Social Development in Childhood and Adolescence provides a full introduction to the theory and research currently underway in this dynamic field."--Provided by publisher.
pt. I. Introduction. 1. Social development: concepts, theory, and overview / Melanie Killen and Robert J. Coplan -- pt. II. Foundations and early beginnings. 2. Biological and social-cognitive bases of emotions. Temperament and social behavior in childhood / Mary K. Rothbart, Stephan A. Ahadi, and Karen L. Hershey -- The development of concern for others in children with behavior problems / Paul D. Hastings [and four others] -- Sympathy through affective perspective taking and its relation to prosocial behavior in toddlers / Amrisha Vaish, Malinda Carpenter, and Michael Tomasello -- A closer look 1: Is biology destiny? The contributions of genetics to social development -- 3. Parent-child attachment relationships. The nature of the child's ties / Jude Cassidy -- Attachment security in infancy and early adulthood: a twenty-year longitudinal study / Everett Waters [and four others] -- The effects of infant child care on infant-mother attachment security: results of the NICHD study of early child care / NICHD Early Child Care Research Network -- A closer look 2: How do I love thee? Attachment and romantic relationships -- 4. Mental states and theory of mind. Mind-reading, emotion understanding, and relationships / Judy Dunn -- Twelve-month-old infants interpret action in context / Amanda L. Woodward and Jessica A. Sommerville -- Scaling of theory-of-mind tasks / Henry M. Wellman and David Liu -- A closer look 3: Autism and theory of mind: understanding others' beliefs, desires, and emotions -- pt. III. Self, relationships, and social groups. 5. Children's peer relationships. The power of friendship: protection against an escalating cycle of peer victimization / Ernest V.E. Hodges [and three others] -- Children's social constructions of popularity / A. Michele Lease, Charlotte A. Kennedy, and Jennifer L. Axelrod -- Group status, group bias, and adolescents' reasoning about the treatment of others in school contexts / Stacey S. Horn -- A closer look 4: Leaders and followers: peer pressure in adolescence -- 6. The development of morality. The development of children's orientations toward moral, social, and personal orders: more than a sequence in development / Elliot Turiel -- Consistency and development of prosocial dispositions: a longitudinal study / Nancy Eisenberg [and five others] -- Children's thinking about diversity of belief in the early school years: judgments of relativism, tolerance, and disagreeing persons / Cecilia Wainryb [and four others] -- A closer look 5: Learning the moral of the story: education in the moral domain -- 7. Self identity and group identity. Changes in children's self-competence and values: gender and domain differences across grades one through twelve / Janis E. Jacobs [and four others] -- Ethnic identity and the daily psychological well-being of adolescents from Mexican and Chinese backgrounds / Lisa Kiang [and four others] -- The development of subjective group dynamics: children's judgments of normative and deviant in-group and out-group individuals / Dominic Abrams, Adam Rutland, and Lindsey Cameron -- A closer look 6: Who am I and what group do I belong to? Self identity in the context of sockal interactions -- pt. IV. Peer rejection and exclusion. 8. Shyness and social withdrawal. Don't fret, be supportive! Maternal characteristics linking child shyness to psychosocial and school adjustment in kindergarten / Robert J. Coplan, Kimberley A. Arbeau, and Mandana Armer -- Trajectories of social withdrawal from middle childhood to early adolescence / Wonjung Oh [and five others] -- Social functioning and adjustment in Chinese children: the imprint of historical time / Zinyin Chen [and three others] -- A closer look 7: But I like to be alone! Unsociability and the benefits of solitude -- 9. Aggression and bullying. An integrated model of emotion processes and cognition in social information processing / Elizabeth A. Lemerise and William F. Arsenio -- A short-term longitudinal study of growth of relational aggression during middle childhood: associations with gender, friendship intimacy, and internalizing problems / Dianna Murray-Close, Jamie M. Ostrov, and Nicki R. Crick -- A peek behind the fence: naturalistic observations of aggressive children with remote audiovisual recording / Debra J. Pepler and Wendy M. Craig -- A closer look 8: A slap in the "Facebook": the study of cyber-bullying -- 10. Stereotyping, prejudice, and exclusion. Children's social reasoning about inclusion and exclusion in gender and race peer group contexts / Melanie Killen and Charles Stangor -- The development and consequences of stereotype consciousness in middle childhood / Clark McKown and Rhona S. Weinstein -- In-group and out-group attitudes of ethnic majority and minority children / Judith A. Griffiths and Drew Nesdale -- A closer look 9: Stereotyping and discrimination: what factors help to reduce prejudice? -- pt. V. Family, community, and culture. 11. Parenting attitudes and beliefs. The company they keep: relation of adolescents' adjustment and behavior to their friends' perceptions of authoritative parenting in the social network / Anne C. Fletcher [and three others] -- Individual differences in adolescents' beliefs about the legitimacy of parental authority and their own obligation to obey: a longitudinal investigation / Nancy Darling, Patricio Cumsille, and M. Loreto Martínez -- Domain-specific antecedents of parental psychological control and monitoring: the role of parenting beliefs and practices / Judith G. Smetana and Christopher Daddis -- A closer look 10: Bridging the generation gap: promoting healthy parent-adolescent relationships -- 12. Culture, ethnicity, and rights. Parents' goals for children: the dynamic coexistence of individualism and collectivism in cultures and individuals / Catherine S. Tamis-LeMonda [and five others] -- Muslim and non-muslim adolescents' reasoning about freedom of speech and minority rights / Maykel Verkuyten and Luuk Slooter -- Chinese adolescents' reasoning about democratic and authority-based decision making in peer, family, and school contexts / Charles C. Helwig [and three others] -- A closer look 11: African-American culture: understanding the past to make predictions about development.
"Edited by two leading scholars, Social Development in Childhood and Adolescence brings together the most significant classic and contemporary writings in this area to provide a comprehensive overview of this dynamic field. Provides all that is needed for teaching social development with the selection of key topics for a 13-week semester, an introductory chapter with an overview of the field and key questions, introductory text for each of 5 sections that contain 3 articles each for a total of 36 articles, with extra materials including discussion questions and classroom exercises Covers key topics such as genetics, temperament, attachment, prosocial development, theory of mind, peer relationships, morality, identity, social withdrawal, aggression, exclusion, stereotyping, parenting, and culture. Addresses issues related to culture, ethnicity, immigration, and diversity Provides a historical, conceptual, and theoretical overview of social development in the introductory chapter Includes introductory sections by the editors for each weekly topic which define key terms and highlights important conceptual issues Integrates helpful pedagogical material throughout: feature boxes highlight current hot topics and real-world applications; end-of-chapter questions, debate topics, and in-class exercises facilitate student understanding and classroom discussion"--Provided by publisher.
Keywords: Child development; Adolescence -- Social aspects; Socialization; Developmental psychology